Porcine pericardial decellularized matrix bilayer patch containing adipose stem cell-derived exosomes for the treatment of diabetic wounds - Wei Liang; Huiting Wu; Lindan Tan; Xiaoyu Meng; Wanwen Dang; Meng Han; Yonghuan Zhen; Haifeng Chen; Hongsen Bi; Yang An (Materials Today Bio)
Chronic hard-to-heal wounds pose a significant threat to patients' health and quality of life, and their clinical management remains a challenge. Adipose-derived stem cell exosomes (ADSC-exos) have shown promising results in promoting diabetic wound healing. However, effectively enhancing the retention of exosomes in wounds for treatment remains a key issue that needs to be addressed. There is a pressing need to develop new materials or methods to improve the bioavailability of exosomes. Porcine pericardium, an extracellular matrix-rich tissue, is easily obtainable and widely available. Decellularized porcine pericardium removes cellular components while retaining an extracellular matrix that supports cellular growth, making it an ideal raw material for preparing wound dressings. In this study, we developed porcine pericardial decellularized matrix bilayer patches loaded with ADSC-exos, which were transplanted into diabetic mouse skin wounds. Histological and immunohistochemical analyses revealed that these bilayer matrix patches accelerate wound healing by promoting granulation tissue formation, re-epithelialization, stimulating vascularization, and enhancing collagen production. In terms of the underlying biological mechanism, we found that decellularized extracellular matrix bilayer patches loaded with ADSC-exos enhanced the proliferation and migration of human dermal fibroblasts (HDFs) and HaCaT cells in vitro, and promoted tube formation in human umbilical vein endothelial cells (HUVECs). This research demonstrated that the porcine pericardial decellularized matrix is well-suited for exosome delivery and that these bilayer patches hold great potential in promoting diabetic wound healing, providing evidence to support the future clinical application of ADSC-exos.